Two peculiar fast transients in a strongly lensed host galaxy. (April 2018) - Rodney, S.; Balestra, I.; Bradac, M.; Brammer, G.; Broadhurst, T.; Caminha, G.; Chirivì, G.; Diego, J.; Filippenko, A.; Foley, R.; Graur, O.; Grillo, C.; et al.
Abstract A massive galaxy cluster can serve as a magnifying glass for distant stellar populations, as strong gravitational lensing magnifies background galaxies and exposes details that are otherwise undetectable. In time-domain astronomy, imaging programmes with a short cadence are able to detect rapidly evolving transients, previously unseen by surveys designed for slowly evolving supernovae. Here, we describe two unusual transient events discovered in a Hubble Space Telescope programme that combined these techniques with high-cadence imaging on a field with a strong-lensing galaxy cluster. These transients were faster and fainter than any supernovae, but substantially more luminous than a classical nova. We find that they can be explained as separate eruptions of a luminous blue variable star or a recurrent nova, or as an unrelated pair of stellar microlensing events. To distinguish between these hypotheses will require clarification of the cluster lens models, along with more high-cadence imaging of the field that could detect related transient episodes. This discovery suggests that the intersection of strong lensing with high-cadence transient surveys may be a fruitful path for future astrophysical transient studies. Two unusual transient events, discovered by Hubble behind a strong-lensing galaxy cluster, can be explained as separate eruptions of a luminous blue variable star or a recurrent nova, or as an unrelated pair of stellar microlensing events.